Type 2 Diabetes Patients’ Need for Physical Activity Programming: A Qualitative Study at a Yogyakarta Hospital Clini - Arovah, Novita Intan; Kushartanti, Bernadeta Wara; Washington, Tracy L; Heesch, Kristiann C (Kesmas, 2019)
Physical activity programs offered in Indonesian hospitals are often inadequate to help type 2 diabetes (T2D) patients meet international physical activity recommendations. This study aimed to identify T2D patients’ physical activity enablers and barriers, their preferences for, and experiences with, physical activity programming, with a view to developing future programs that are suited to these patients’ needs and preferences. Four focus groups were conducted with 28 patients (50% female) of the T2D clinic at the Local General Hospital of Yogyakarta. Discussions were thematically analysed in NVivo 10. The most reported types of physical activity were walking and participation in the hospital-based exercise program. Participants were motivated to be physically active for the health benefits and for social interactions. The main barriers to physical activity were a lack of enjoyment, the absence of knowledge about appropriate activities for T2D patients, and a shortage of time due to social and family obligations. Based on study participants’ preferences, future physical activity programs need to include educational components, regular clinical evaluations, consultations with health educators, and efforts to increase the reach of the programs. This study provides practical suggestions for physical activity programming that meet the needs of T2D patients in Indonesia.